Patlau A Typical Food From Pontianak Culture in The Month of Ramadhan and Its Relevance to The Concept of Geometry of Spatial Figures - Mukmin, Chairul; Sarassanti, Yumi (UMBanjarmasin - LP2M UM Banjarmasin, 2024)
n Indonesia, there are many cultures from various regions, making it a diverse country. From culture, of course there are special foods from each region, so Indonesia is known as a country that has many regional specialties. The aim of this research is to observe the food found in various regions and also try to see its relationship to the concept of spatial geometry. This research method uses